Perception du capital immatériel : cas des entreprises cotées basées en Côte d’Ivoire - Ouattara, Abdoulaye; Aka, Franck Anselme (Revue Française d'Economie et de Gestion, 2022)
L’objectif de cet article est d’apprécier la perception du capital immatériel par les dirigeants et investisseurs des entreprises cotées basées en Côte d’Ivoire. En effet, malgré l’importance de ces composantes pour les entreprises, et malgré surtout les recommandations faites par certains chercheurs en général pour sa divulgation, un grand nombre des composantes du capital immatériel n’est pas pris en compte par la comptabilité de notre système comptable OHADA; D’où l’intérêt de cette étude. Pour ce fait, la théorie du signal a été mobilisée et une étude exploratoire a été menée. A travers une enquête exploratoire menée auprès de 48 acteurs, composés de 22 investisseurs et de 26 managers, les résultats révèlent que le capital immatériel, bien que très important, n’est pas réellement pris en compte dans le management de ces entreprises. Pour ces dirigeants et investisseurs, il est très important d’intégrer cette dimension pour la pérennité des entreprises, car ils le perçoivent comme un outil d’aide à la décision et de valorisation des entreprises.
Keywords: Capital immatériel; Divulgation d'informations; Entreprises cotées; Information disclosure; Perception; Valorisation des entreprises

La bonne foi et l’intérêt social au soutien de la protection du dirigeant de société, Com., 30 mars 2022, nos 20-16.168 et 20-17.354. - Dumont, Roman (Revue Juridique de la Sorbonne, 2022)

Corporate Governance and Women on the Board of Directors : the Legal Framework towards a Minimum Harmonisation in the European Union - Lamy Martin, Joy (Université Paris-Saclay, 2022)
This thesis concerns the recent and considerable change in corporate governance legislation, specifically how boards of directors address the issue of parity and the appointment of its members in public limited companies. This research will challenge European Union law which, to date, does not propose EU harmonization.The UK, France, Germany and Norway (a non-member country but one that will be included in this research) have introduced changes to their national legislation in relation to company boards in public listed companies. This research will focus on a comparative study of parity on company boards under European Union law and its application in the UK (pre-Brexit), Germany, France and Norway. The application of corporate governance codes or soft law and the proposal for a hard law directive demonstrate a fragmentation in the EU, as the application of law by hard quotas divides member states and parliamentarians in European Union law. Corporate governance law in the member states varies considerably, but it must respect the EU's primacy law. Comparisons of legislation between member states reveal the marked differences in law.Women are significantly under-represented on the corporate boards of public limited companies in Europe. Legitimate questions need to be asked. Does the European Commission have the right to make a proposal for a directive allowing for parity on the boards of public limited companies in the EU? The reality is that the Commission does not have a solid approach in dealing with the issue of parity. As long as there is too much inconsistency between Member States, this leaves considerable room for further research. Legislation and governance law between member EU member states diverge considerably and demonstrate inconsistency with the legislation between them, resulting in little or no consensus in the interpretation of EU law. Or member states diverge with opposing interpretations of EU law, especially concerning sovereignty.National legal systems differ considerably in the way legislation allows for the appointment of board members and the notion of parity. A review of corporate governance matters concerning shareholders, the composition and appointment of board members corporate governance codes reveal the gap between member states. The research focus on parity by way of a comparison of the soft and hard laws of the member states.. The research upholds European law Article 157(3) Treaty of the Functioning on the European Union (TFEU), which is the fundamental principle of EU law and basis of gender equality and parity.The research will contribute to raising awareness of this issue through quota legislation and the question of parity on boards in public limited companies in the EU.
Keywords: Board of directors; Comparative Law; Conseil d'administration; Corporate Governance; Droit comparé; Gender and parity; Genre et parité; Gouvernance des entreprises; Quotas; The European Union; Union européenne

Précisions jurisprudentielles sur la notion et la sanction de l’unanimité en droit des sociétés, Cass. com., 5 janvier 2022, no 20-17.428, publié au Bulletin - Schlumberger, Edmond (Revue Juridique de la Sorbonne, 2022)

Les conflits d'intérêts en droit des sociétés - Boucant, Nicolas (Université Paris 12, 2022)
De sa création jusqu’à son terme, la société peut faire face à des interférences entre ses intérêts, d’une part, et les intérêts des associés, des dirigeants et des personnes auxquelles ils sont liés, d’autre part. En droit des sociétés, la genèse des conflits d’intérêts réside dans la volonté des associés et des dirigeants de privilégier leurs intérêts ou ceux d’une personne à laquelle ils sont liés, au détriment de l’intérêt social. Cette recherche a pour objectif de proposer une grille de lecture juridique renouvelée de la notion de conflit d’intérêts, articulée autour du préjudice et du devoir de loyauté. Elle met en évidence une méthodologie afin de définir le conflit d’intérêts en droit des sociétés. La présente étude identifie avec précision les mécanismes pratiques de détection, de prévention, de gestion, de sanction et de réparation des conflits d’intérêts.
Keywords: Company; Conflicts of interests; Conflits d’intérêts; Corporate law; Damage; Droit des sociétés; Interests; Intérêt social; Intérêts; Loyalty; Loyauté; Pouvoir; Power; Préjudice; Règlement de conflits; Sociétés

La régulation des entreprises multinationales en Afrique subsaharienne : De l'instrumentalisation à la prise en compte d'un développement collectif durable par les stratégies RSE (Responsabilité Sociale de l'Entreprise) - Monemou, Adama Esperance (Université de Toulon, 2022)
Du fait de son pouvoir de régulation, la Responsabilité Sociale de l’Entreprise (RSE) est foncièrement un instrument au service du développement durable. Ainsi, l’émergence et la diffusion de cet instrument en Afrique subsaharienne doit répondre à plusieurs besoins, au premier rang desquels figurent la réalisation des Objectifs du Développement Durable (ODD) et la contribution à l’atteinte des Objectifs du Millénaire pour le Développement (OMD). C’est dans cette perspective que les entreprises multinationales trouvent leur place et sont visées par le champ normatif de la RSE. Le questionnement éthique et social des entreprises multinationales en Afrique subsaharienne conduit inéluctablement à rechercher différents leviers de régulation sous les trois (3) aspects, à savoir environnemental, social et économique, pour la mise en œuvre opérationnelle de la RSE. Sans occulter le foisonnement d’initiatives RSE, y compris les démarches volontaires des entreprises multinationales souvent matérialisées par les codes de conduite, un système de régulation contraignant semble se configurer à l’échelle internationale sous l’impulsion des organisations internationales, la pression des ONG et des parties prenantes dont les investisseurs. Par conséquent, les entreprises multinationales, soucieuses de préserver leur image, leur légitimité ainsi que l’ancrage dans les territoires d’implantation, doivent garantir la transparence et la cohérence des pratiques, face au manque d’effectivité souvent constaté des discours RSE qui ne répondent qu’aux finalités marketing et commerciale. Cette instrumentalisation justifie l’immixtion du droit et la construction progressive d’un véritable droit de la RSE, avec une approche à la fois réglementaire tendant à favoriser la production de normes à caractère contraignant, du moins exemptes de toute instrumentalisation et stratégique en procurant un avantage compétitif aux entreprises engagées en RSE par la voie de la consommation responsable et pour que celles-ci apportent une contribution au développement collectif durable des territoires d’implantation.
Keywords: Afrique subsaharienne; Corporate Social Responsibility; Droits de l'homme; Développement durable; Entreprises multinationales; Human rights; Instrumentalisation; Instrumentalization; Millenium development goals; Multinational companies; Objectifs du développement durable; Objectifs du millénaire pour le développement; Regulation; Responsabilité sociale de l'entreprise; Responsabilité sociétale des entreprises multinationales; Régulation; Sub-Saharan Africa; Sustainable development goals

A interdisciplinaridade do Direito Societário e do Direito Tributário: da desvinculação do balanço societário para fins tributários. O lucro contábil das concessionárias de serviços públicos de transmissão de energia elétrica - Ippolito, Marcelo Baeta (Universidade de São Paulo, 2022)
O tema que envolve as diferenças entre o lucro contábil para fins societários e para fins tributários é sempre polêmico, ainda que o lucro, para fins societários, no Brasil, seja utilizado como ponto de partida para a determinação da base de cálculo do imposto sobre a renda das pessoas jurídicas. Nesta tese, entretanto, estas diferenças serão abordadas sob ângulos diferentes e com base em situações contemporâneas e pragmáticas que expõem, com maior profundidade e clareza, as razões e fundamentos delas, de modo que, a despeito da reconhecida contribuição da interdisciplinaridade envolvendo o direito societário e a contabilidade e, por outro lado, o direito societário e o direito tributário, tendo como objeto de conhecimento o referido lucro contábil, será possível, especialmente por conta das novas dificuldades trazidas pela introdução do novo padrão contábil no Brasil, provar a conveniência e a necessidade da desvinculação do lucro contábil e suas respectivas regras de apuração, nos termos da legislação societária, para efeito de consideração como ponto de partida, de acordo com as regras atuais, para apuração da base de cálculo do imposto sobre a renda das pessoas jurídicas. Nesse sentido, inicialmente, o caminho a ser trilhado no presente trabalho de pesquisa e desenvolvimento da tese de doutorado é determinado pela consideração do direito como objeto cultural, criado pelo homem e, como tal, para ser conhecido e apreendido, necessário se faz a sua expressão em linguagem. Por outro lado, importante abordagem do tema levará em consideração que há independência da linguagem em relação à realidade, bem como que a mesma linguagem constitui a realidade conceptual que, por sua vez, é a única passível de ser objeto de conhecimento. Portanto, é possível afirmar que uma das contribuições originais da tese corresponde a essa abordagem do lucro como uma realidade conceptual, constituída pela linguagem contábil, na medida em que será capaz de fornecer maiores subsídios e elementos para melhor se mensurar as dificuldades do compartilhamento desse objeto de conhecimento pelo direito societário e tributário, promovido pela interdisciplinaridade desses ramos do direito, especialmente quando a realidade conceptual que atende aos interesses específicos do direito societário se distanciou enormemente da realidade conceptual que se quer regular por meio do direito tributário, tendo em vista a aplicação de novas normas sintáticas, semânticas e pragmáticas da linguagem contábil. Para efeito de se demonstrar o distanciamento das realidades conceptuais correspondentes aos objetos de conhecimento do direito societário e tributário, a utilização das demonstrações financeiras das Concessionárias de Serviços Públicos de Transmissão de Energia Elétrica como parâmetro traz, também, originalidade à tese, correspondendo à prova efetiva de como a utilização do lucro contábil societário, também para fins tributários, pode gerar mais dificuldades para ambas as áreas do direito do que contribuições positivas.
Keywords: Accounting; Concessionaires; Concessionárias; Contabilidade; Interdisciplinaridade; Interdisciplinarity; Lucro; Profit; Public Utilities; Serviços Públicos

Perspectives mélioratives de certains aspects de la gouvernance des compagnies d’assurance dans l'espace CIMA - Ekande, Fréderic (International Multilingual Journal of Science and Technology, 2022)
La succession des scandales financiers ayant secoués le monde des affaires n’ont pas laissé les gouvernants encore mois les propriétaires des capitaux indifférents. Les dirigeants sociaux, qui jusqu’à une certaine époque se prévalaient de tous les droits pour donner une bonne réputation aux entreprises qu’ils dirigeaient, ont connu une déchéance inattendue. En réalité, les actionnaires propriétaires des entreprises ont compris qu’avec la recrudescence des scandales financiers qu’il était temps de reprendre les choses en main, d’où la vulgarisation et l’application des principes de gouvernance d’entreprise. Si le secteur de l’assurance de la CIMA, n’a pas connu des affaires rocambolesques il n’en demeure pas moins que le législateur communautaire a considéré cet aspect de la gestion comme important d’où la reforme survenu en 2009 dans le code des assurances. La gouvernance d’entreprise, tente tant bien que mal à réparer les dégâts les plus insupportables que certains esprits malveillants n’ont cessé de causer. Beaucoup s’interrogent alors, sur les moyens de limiter les effets néfastes de certaines habitudes, qui sont à la base du dysfonctionnement des entreprises. Si les soubassements ont été posé par le code des assurances de la CIMA, il est évident qu’en ayant un regard prospectif sur l’assurance de demain certains aspects de la gouvernance d’entreprise peuvent être amélioré afin d’atteindre les objectifs de bonne gouvernance. The series of financial scandals that have shaken the business world have not left the rulers, let alone the owners of capital, indifferent. Corporate managers, who until a certain time had every right to give a good reputation to the companies they managed, have experienced an unexpected decline. In fact, the shareholders who own the companies realised that with the increase in financial scandals it was time to take things in hand, hence the popularisation and application of corporate governance principles. Although the CIMA insurance sector has not experienced any scandalous affairs, the fact remains that the community legislator has considered this aspect of management to be important, hence the reform of the insurance code in 2009. Corporate governance is trying as best it can to repair the most unbearable damage that certain malevolent spirits have continued to cause. Many people are now wondering how to limit the harmful effects of certain habits that are at the root of corporate dysfunction. If the foundations have been laid by the CIMA insurance code, it is obvious that by looking ahead to the insurance of tomorrow, certain aspects of corporate governance can be improved in order to achieve the objectives of good governance.
Keywords: CIMA; Code de bonne gouvernance; Code of good governance; Compagnie d’assurance; Corporate governance; Gouvernance d'entreprise; Insurance company; Transparence; Transparency

La société en participation dans l’espace OHADA à l’épreuve de la lutte contre l’économie informelle en République Démocratique du Congo - Bonzeke Iliki, Freddy (Cahiers Africains des Droits de l’Homme et de la Démocratie ainsi que du Développement Durable, 2022)
De toute évidence, la lutte contre le secteur informel en RDC constitue l'un des facteurs de la dynamisation de l'économie nationale. Cette lutte nécessite que les mesures idoines soient prises, entre autres l'engorgement de tous les canaux de facilitation des activités économiques informelles, à travers les règles claires dont la violence est sévèrement sanctionnée de manière à dissuader tous les récalcitrants. En effet, parmi les mesures juridiques prises par le législateur de l’OHADA figure la consécration des sociétés commerciales pouvant fonctionner sans personnalité juridique, c'est-à-dire de façon informelle, dont la société en participation. Et plusieurs se cachent derrière ces formes de sociétés pour légitimer leurs activités informelles, tout en se soustrayant du contrôle étatique. Cette étude vient apporter la lumière quant à ce. Elle précise que la consécration de la société en participation, comme pour les autres sociétés sans personnalité juridique, n'est pas à concevoir comme un moyen d'encourager les opérateurs économiques à y recourir, mais une sanction à l'encontre de ceux qui auraient donné l'impression d'avoir constitué une société commerciale et voudraient se soustraire des obligations qui en découlent, en évoquant l'absence de la personnalité juridique. Ainsi, il est important que le législateur renforce les sanctions contre tous ceux qui s'y livrent de manière à ne pas permettre la dénaturation de sa réforme.
Keywords: Acte uniforme; Contrat; Economie informelle; Immatriculation; Participation; Société

Analysis of the Determinants of the Effectiveness of the Board of Directors in Family Businesses in Cameroon - Roukatou, Aboubakar; Dretti, Denise (Open Journal of Business and Management, 2022)
The composition of the Board of Directors is commonly presented as an understandable variable for its effectiveness. However, the work that examined the relationship between the composition and effectiveness of the Board is not characterized, as they require about whether or not certain categories of directors (internal, external, independent) are relevant and the related empirical results are mixed. This work examines the relationship between the characteristics of the board of directors and its effectiveness in a type of business that is very common in the world, respecting the family business. Thus, the problem that this study tries to solve is to identify the characteristics of the board of directors that can contribute to its effectiveness in Cameroonian family businesses. We found that the size of the Board, the presence of external directors, and the cumulative management and control functions appear to have an impact on the effectiveness of the Board.
Keywords: Board of directors; Family Business; Governance; Public Limited Company

The Effects of Covid-19 Crisis on Good Governance at the Local Level, The Case of Tunisia - Braham, Fatma; Seguir, Sonia (Journal of the Association of Arab Universities for Research in Higher Education, 2022)
The COVID-19 crisis, in addition to its serious health impact, has negatively affected key socio-economic aggregates and has shocked the strategic planning of all economic and social actors, including local communities. In search of resilient, skillful and intelligent good territorial governance, the municipalities are working to adapt their governance systems to the new social and environmental priorities. This work proposes a new reading of the acquired approaches to good governance, a new paradigm related to the new conjuncture and an assessment of the performance system at the central and local levels

Le quasi associé en Droit OHADA et Droit Français - Aquereburu, Edouard-Robert (Université Paris 12, 2022)
Ce travail ambitionne d’étudier des notions ayant des droits et un régime proche de celui de l’associé mais auquel le droit ne reconnaît pas la qualité d’associé. Jusqu’ici, la doctrine s’est contentée de définir, de distinguer l’associé de celui qui ne l’était pas. En effet, les auteurs à partir des critères de qualification de l’associé refusent la qualité d’associé au porteur dans le cadre d’une convention de portage. Il existe un débat doctrinal nourri par d'autres auteurs autour de la qualification d’associé de l’usufruitier. A cette idée, rejoignent des fondements textuels qui refusent également, la qualité d’associé aux titulaires de valeurs mobilières donnant accès au capital ainsi qu’aux fiduciaires.Aussi ce travail a pour intérêt de démontrer qu’il existe un cadre commun à plusieurs de ces concepts juridiques existant autour de la notion d’associé au sein du droit français et au sein de l’espace régit par le droit OHADA. La notion de quasi-associé a été encore peu interrogée aussi bien en droit Français qu’en droit OHADA. Largement inspiré du droit français, le droit OHADA recèle quelques particularités en raison du contexte et de la coutume africaine. Ce travail comparatif entre le droit Français et le droit OHADA relèvera les singularités existantes au sein du droit OHADA sur la notion de quasi associé.Deux approches méthodologiques sont mobilisées pour étudier le quasi-associé au sein du droit des sociétés français et de l’espace OHADA.La première approche est de comparer les critères de qualification de l’associé aux concepts juridiques retenus. La seconde approche est de s’appuyer sur les outils jurisprudentiels, textuels et la doctrine afin d’identifier d’autres critères.les concepts juridiques sélectionnés agissent comme étant des associés sans pour autant recevoir la qualification d’associé.Enfin, le travail aura pour objectif final d’identifier les conditions et le régime pour ce quasi-associé. Bref, définir ce qu’est un quasi-associé à la lumière du droit français et du droit OHADA.
Keywords: Associé; Capital investissement; Corporate law; Droit des sociétés; Informal society; Ohada; Partner; Private equity; Securities; Société informel; Valeurs mobilières

La vertiente societaria del contrato de gestión hotelera - Moguel Fernández, Jordi (Universitat de Lleida, 2022)
En aquest treball s’examina, amb l’ajuda d’un estudi de casos múltiples, la naturalesa societària que adquireix aquell contracte de gestió hotelera en què el prestador de serveis és una cadena que implanta el seu model d’empresa en una xarxa d’allotjaments a la qual s’incorpora l’establiment objecte d’aquella relació jurídica. En aquest marc, la perfecció de la modalitat contractual esmentada no només comporta que el gestor de l’allotjament hagi de vetllar pels interessos aliens, sinó també que hagi de salvaguardar i executar les regles que beneficien el conjunt d’explotacions hoteleres que comparteixen uns mateixos intangibles. És en aquest darrer àmbit on sorgeix el “grup de negocis” com una organització de caràcter jeràrquic que pot englobar-se en l’ampli fenomen dels grups de societats, la missió del qual és promoure el prestigi i l’òptim funcionament de la xarxa hotelera per a després traslladar tals beneficis als diferents allotjaments que s’incorporen a l’agrupació mitjançant contractes com el de gestió hotelera. Així mateix, dintre d’aquesta estructura grupal es mantenen relacions associatives entre els seus integrants, cosa que dona lloc a una societat interna en la qual els seus socis assumeixen el compromís de respectar i complir els estàndards de la cadena, així com els serveis grupals que aquesta estableixi amb tal propòsit. Aquesta tesi analitza en profunditat l’esmentada arquitectura jurídicosocietària des de la perspectiva del dret mercantil, prestant atenció principalment al dret de societats i al de la competència, sense deixar de costat el dret d’obligacions i contractes. A més, s’estudien amb deteniment els diferents conflictes intragrup que poden derivar-se de les vicissituds d’aquella complexa estructura organitzativa, davant dels quals es proposen diversos remeis jurídics a partir de solucions que ofereix el dret espanyol.
Keywords: Conflictes intragrup; Conflictos intragrupo; Contracte de gestió hotelera; Contrat de gestion; Contrato de gestión hotelera; Dret Mercantil; Gestion hôtelière; Group of companies; Grup de societats; Grupo de sociedades; Hotel management agreement; Hôtel; Intragroup conflicts

الحماية المدنية لقواعد حوكمة الشركات التجارية المتعلقة بمحافظي الحسابات - معمر, خالد; شارف, بن يحي (مجلة البحوث في الحقوق والعلوم السياسية, 2022)
يتضمن هذا البحث الحديث عن موضوع مهم جدا في مسألة حوكمة الشركات التجارية وهو إظهار مواطن التأثير من قبل محافظ الحسابات و إبراز مبادئ الحوكمة وتحقيقها في الشركة التجارية وما يتبعها من وعي لدى أصحاب المصالح وما ينتج عنه من زيادة الثقة في تعاملات الشركة وربحيتها ،لذلك تم الاهتمام بفحص النصوص المنظمة لتعيين محافظي الحسابات وبيان مهامهم ومسؤولياتهم وتقدير كفاية الحماية المدنية التي تحتوي عليها هذه النصوص ومدى ملاءمتها وخدمتها لقواعد الحوكمة. ومن ناحية أخرى حوكمة المسؤولية في حد ذاتها من خلال توقيعها على محافظي الحسابات الذين يستحقون حقا المساءلة وإعفاء من قاموا بواجباتهم التي فرضها القانون على أتم وجه من خلال تكريس القواعد التي تعفي من المسؤولية والأخرى التي تأمنهم منها. This research includes talking about a very important topic in the issue of business governance, which is to show the influence of the portfolios of accounts and to highlight the principles of governance and its realization in the commercial company and the subsequent awareness of stakeholders and the resulting increased confidence in the company's dealings and profitability, so attention was paid to examining the texts governing the appointment of account governors and showing their functions and responsibilities and assessing the adequacy of civil protection contained in these texts and their suitability and service to governance rules. On the other hand, governance of responsibility per se by signing it to the auditors who truly deserve accountability and exempting those who have fully carried out their duties imposed by law by enshrining the rules that exempt them from liability and those from which they are safe.
Keywords: Comptable; Développement; Gouvernance d'entreprise; Responsabilité civile; التنمية; حوكمة الشركات; محافظ الحسابات; مسؤولية مدنية

L'éviction des associés d'une société en difficulté - Thiéry, Emilie (Université Paris 1, 2022)
Le traitement des associés d’une société en difficulté repose sur l’application cumulative du droit des sociétés et du droit des procédures collectives. Cette cohabitation, sans tentative de synchronisation, ne résiste pas au test de cohérence entre le droit des procédures collectives, qui aménage les droits patrimoniaux des associés, et le droit des sociétés, qui maintient par principe leurs droits extra-patrimoniaux. Cette situation conduit à conférer aux associés, pourtant titulaire d’une créance de dernier rang, un droit de blocage d’un plan de reprise interne alors que les créanciers sont tenus de consentir des sacrifices. La présente étude a pour objet de trouver une ligne de démarcation entre opposition légitime des associés pour préserver leurs droits et leur nécessaire éviction dans le cadre de l’adoption du plan de reprise interne. La clé de voûte de la réconciliation du droit des sociétés et du droit des procédures collectives, quant au sort des associés d’une société en difficulté, est leur engagement commun de contribuer aux pertes. Cette analyse renouvelée autour de la créance de dernier rang de l’associé implique que toutes les parties affectées, dont les associés, votent les mesures de reprise interne proposées, réunies au sein de classes partageant des caractéristiques homogènes. Ces nouveaux outils consacrés, selon une cohérence retrouvée, permettront de dynamiser les plans reposant sur la reprise interne de la société.
Keywords: Actionnaires; Associés; Company law; Corporate law; Droit des procédures collectives; Droit des sociétés; Entreprises en difficulté; Eviction; Insolvency law; Relations avec les actionnaires; Shareholders

La conversion des créances du débiteur en capital social - Tchimtchoua Fotso, Keyolle Vanesta (International Multilingual Journal of Science and Technology, 2022)

Interpretação do contrato social e do estatuto social no direito societário - Portugal, Daniel Ochsendorf (Universidade de São Paulo, 2022)
Não se deve dizer que o controlador ou que a maioria seria o intérprete do interesse social. Qualquer um, em princípio, pode interpretar o contrato social ou o estatuto social - se o intérprete está certo ou não, isto é outra questão -, e os controladores também podem vir a violar o contrato de sociedade. O contratualismo pode ser associado a algo que dá importância para o contrato social ou para o estatuto social enquanto o institucionalismo pode ser associado a algo que não dá relevância para o contrato social ou para o estatuto social e que, supostamente, se preocupa apenas com o interesse público. Parte do problema do institucionalismo é que o negócio de sociedade termina por ser de algum modo enaltecido exageradamente. As sociedades, certamente, têm um impacto muito forte nas vidas das pessoas em geral, porém os aspectos negociais das sociedades não devem ser deixados de lado - eles são a origem das sociedades
Keywords: Articles of incorporation and bylaws; Contrato social e estatuto social; Corporate law; Direito das sociedades; End of corporations and interests of corporations; Estado de Direito; Fim social e interesse social; Interpretation; Interpretação; Interprétation; Rule of Law; Règlement; Société; Statuts

A desconsideração da personalidade jurídica e os sócios não gestores da sociedade limitada - Ferraz, Fábio Garcia Leal (Universidade de São Paulo, 2022)
A tese objetiva estudar os impactos do instituto da desconsideração da personalidade jurídica aos sócios não gestores da sociedade limitada, após a recente redação da Lei da Liberdade Econômica, que positivou, entre outras situações, o benefício como critério de responsabilização. Dividido em três partes e se valendo da metodologia analítica dedutiva e indutiva, o presente trabalho aborda, no primeiro capítulo, a responsabilidade pelos atos da sociedade limitada, utilizando como base obras importantes, como as de Calogero Gangi, Federico de Castro y Bravo, José Waldecy Lucena, Itamar Gaino e Júlio César Lorens. O capítulo intermediário trata do instituto da desconsideração propriamente dito, trazendo um esboço histórico, alterações legislativas, requisitos de aplicação e direito comparado, se valendo das principais obras sobre o assunto, como as de Rolf Serick, Piero Verrucoli, Rubens Requião e José Lamartine Corrêa de Oliveira, entre outras. No capítulo final, adentra-se a temática central, com o estudo aprofundado do nível de responsabilização dos sócios não gestores quando instaurado o incidente de desconsideração da sociedade limitada (responsabilização subjetiva). Viu-se no estudo que a positivação do critério do benefício não foi uma escolha isenta de críticas, apesar de se tratar de um avanço. No entanto, os sócios não gestores continuam expostos a uma possível responsabilização ilimitada juntamente com os demais sócios gestores e infratores quando aplicada a desconsideração. Ao final do estudo, sugere-se um novo caminho, com uma cláusula híbrida de responsabilização dos sócios, na esperança de contribuir e aprofundar a matéria, pois o impacto gerado pelo instituto aos sócios não gestores é muito pouco explorado, apesar da importância desse tipo de sócio para o investimento passivo nas sociedades brasileiras.
Keywords: Accountability; Associé; Benefit; Benefício; Desconsideração da personalidade jurídica; Disregard of legal entity; Economic Freedom Law; Lei da Liberdade Econômica; Limited company; Non-managing partners; Nongérant; Responsabilização; Sociedade limitada; Société à responsabilité limitée; Sócios não gestores

Mineur et société de famille - Dasque, Marie (Université de Pau et des Pays de l'Adour, 2022)
En tant que personne vulnérable, le mineur bénéficie traditionnellement de règles protectrices et parfois contraignantes destinées à protéger sa personne et son patrimoine. Or, ces dernières se trouvent mises à mal lorsque la qualité d'associé vient se superposer à celle d'incapable. Or il n'est pas rare aujourd'hui qu'un mineur acquière la qualité d'associé, que ce soit lors de la constitution de la société ou en cours de vie sociale. Il peut en effet entrer en société soit par le choix de ses parents, soit en qualité d'héritier d'un associé défunt. En outre, la société, en tant que personne morale sans lien avec les personnes qui la composent, est régie par des règles de fonctionnement qui lui sont propres et qui sont quasiment muettes sur cet associé particulier. II est alors primordial d'apprécier la protection accordée à l'associé mineur dans le cadre particulier des sociétés de famille, c'est-à-dire des sociétés constituées entre membres d'une même famille. Cette protection dépend de la combinaison du droit des mineurs et en particulier des règles de la représentation et du droit des sociétés. Il s'avère que cette combinaison permet parfois aux représentants de l'enfant d'assurer la protection du mineur en exploitant les avantages du droit des sociétés ou en comblant les lacunes. Mais il peut s'avérer que cette combinaison se réalise au détriment des règles de protection et de représentation du mineur. Il est notable que la combinaison des deux corps de règles se réalise différemment selon que la société est constituée dès l'origine autour du mineur ou que la question de l'entrée du mineur se pose après sa constitution. En effet, lorsque la société est conçue autour du mineur, il apparaît que les représentants légaux ont une marge de manoeuvre importante au regard du droit des sociétés : soit qu'il s'agisse de tirer parti des avantages du recours à la forme sociale, soit qu'il s'agisse d'assurer la protection des intérêts du mineur associé que le droit des sociétés ne prend pas en considération sauf exceptionnellement pour lui fermer certaines formes sociales. A l'inverse, lorsque la société subit l'arrivée du mineur, le droit des sociétés manifeste sa supériorité sur le droit de la représentation des mineurs qu'il s'agisse d'organiser les conditions de son acceptation en tant qu'associé ou de lui refuser l'entrée dans la société.C'est ce que la thèse entend démontrer.
Keywords: Famille; Family company; Jeunesse -- Protection, assistance, etc; Mineur; Mineurs (droit); Minor; Protection; Société de famille

Performances des entreprises sénégalaises et réformes dans l'environnement des affaires - Diagne, Idrissa (Université Cheikh Anta Diop, 2022)
L’objectif de ce travail consiste à étudier les réformes et la performance des entreprises sénégalaises. Nous avons à cet effet utilisé l’analyse en composante principale (ACP) suivie d’une classification ascendante hiérarchique (CAH) afin de définir la structure des entreprises sénégalaises et la typologie du tissu des entreprises des pays de référence. Les résultats obtenus nous ont permis de conclure que la taille de l’entreprise est un déterminant de sa position géographique, de son âge et de la participation des capitaux étrangers. Toutefois, aucun lien n’a pu être décelé entre la taille et le régime d’exportation. Ensuite, nous avons pu déterminer que la typologie du tissu des entreprises du Sénégal est loin de refléter celle des pays de référence. De plus, à partir de la méthode de régression linéaire simple (OLS), nous avons relevé que la position géographique, le statut juridique, le transfert de technologie, l’innovation et l’ouverture aux nouveaux marchés, affectent positivement la valeur ajoutée de l’entreprise. En revanche, la taille de l’entreprise, le secteur d’activité, la participation de l’État dans le capital, les garanties sur les prêts influent négativement sur la valeur ajoutée des entreprises. Enfin, à partir de la méthodologie d’analyse comparative, nous avons tiré des leçons sur les meilleures pratiques en termes de réformes. Les résultats suggèrent que l’État du Sénégal devrait davantage s’orienter vers la réduction des coûts afférant à la création d’entreprise, notamment, les frais de notaire, les droits d’enregistrement et la réduction des taxes. L’État devrait également diminuer les coûts de l’énergie, les pertes énergétiques et se réorienter davantage vers le mix-énergétique. En outre, il pourrait améliorer l’accès aux financements à travers le renforcement de l’information sur le crédit, l’acquisition d’actifs et la règle de l’insolvabilité. L’État pourrait par ailleurs renforcer le développement des infrastructures, notamment, aéroportuaire, ferroviaire. D’autre part, la mise en œuvre d’une stratégie nationale de réformes foncières devrait lui permettre de sécuriser le foncier. L’accent devrait être mis ainsi sur l’enseignement professionnel, à l’image du Rwanda et doter le pays d’un système intégré d’informations sur l’emploi. Afin de renforcer la compétitivité des entreprises sénégalaises, l’État gagnerait à renforcer un système national intégré de qualité, et à promouvoir le “label made in Sénégal” à l’image du Rwanda et de l’Éthiopie.
Keywords: Affaires; Entreprise (performance); Entreprise (taille); Secteur manufacturier; Sénégal; Valeur ajoutée

Do corporate governance codes matter in Africa? - Areneke, Geofry; Khlif, Wafa; Kimani, Danson; Soobaroyen, Teerooven (Research Handbook on Corporate Board Decision-Making, 2022)
Africa is often depicted in the literature as the ‘patron late to the party’ on account of her low uptake of corporate governance codes. Notwithstanding, countries that have an existing corporate governance code continue to exhibit weak corporate accountability and governance practices. This prompted a critical analysis based on a detailed review of published articles and existing codes in the African multiple-contexts. Our findings reveal that the efficacy of many codes remains very limited in terms of pragmatic outcomes whilst firms in countries that have adopted codes continue to face uneven performance and poor accountability. We conclude by urging for an understanding of the reasons underlying such results. We recommend an African led re-think (independence, ownership, board processes) of existing codes to make them more aligned with the governance needs of African firms and their complex sociocultural background. We call for further research to illuminate Africa’s actual governance experiences and necessities.
Keywords: Africa; African principles; Board of directors; Boardroom processes; Codes; Corporate governance; Developing countries; Neo-colonialism

Şirketler hukukunun geleceği üzerine bir inceleme: Şirket yönetiminde yapay zekâ - Bora Çinar, Sevda (Akdeniz Üniversitesi, 2022)
Yapay zekâ teknolojileri, insan unsurunun egemen olduğu pek çok alanı etkisi altına almaya hazırlanmaktadır. Bu alanlar arasında tıp, hukuk, eğitim, mühendislik olduğu gibi ticaret de bulunmaktadır. Yapay zekâ teknolojileri, özellikle şirketler hukukunun geleneksel yapısını kökünden sarsacak yeni bir ticari düzen ve anlayış yaratma yolundadır. Karar alma süreçlerini otomatikleştiren yapay zekâ teknolojilerinin verimliliği ve hızı, şirketlerin bu sistemleri geliştirerek pazarlamalarının yanı sıra bizzat şirket bünyelerine katarak kullanma eğilimi göstermelerine de yol açmaktadır. Bu şekilde kendi kendini besleyen bu döngü, yapay zekâ alanına sermaye yapısı güçlü şirketlerin yönelmesini ve araştırma kapsamının gittikçe genişletilmesini sağlamaktadır. Şirketlerdeki bu yönelim neticesinde, hızla gelişen yapay zekâ teknolojilerinin geleneksel şirket yapılarını etkileyebilme potansiyelinin yükselmesi olgusu, şirketler hukukunun geleceği üzerine bir inceleme yapılması gerekliliğini ortaya çıkarmaktadır. Çalışmamızda şirket yönetiminde yapay zekâ teknolojilerinin kullanımına ve bunun hukuki sonuçlarına odaklanılmakta ve konu dört temel bölüme ayrılarak incelenmektedir. Giriş bölümünde kısaca çalışmanın konusu, önemi, amacı, kapsamı ve sistematiği açıklanmakta, yapay zekâ ve şirket yönetiminin kavramsal çerçevesine yer verilmektedir. Birinci bölümde şirketler hukuku ve yapay zekâ teknolojilerinin etkileşimi incelenmektedir. Bu bölümde yapay zekâ teknolojilerinin ticaret hukuku ve şirketler hukuku ile etkileşimi incelenmekte, dijitalleşmenin şirketler hukukuna etkileri, özellikle şirket yapılarındaki ve menfaat çatışmalarındaki dönüşüm çerçevesinde ele alınmaktadır. İkinci bölümde, şirket yönetiminde yapay zekâ teknolojilerinin kullanılması bir süreç olarak incelenmektedir. Kullanım kararı alınmasından başlamak üzere, şirkete uygun yapay zekâ teknolojilerinin edinimi ve bu teknolojilerinin şirket yönetiminde kullanılma yöntemlerinin araştırıldığı bu bölümde, teknik, hukuki ve ticari başta olmak üzere ilgili beklenti ve belirsizlikler araştırılmaktadır. Üçüncü bölümde şirket yönetiminde yapay zekâ teknolojilerinin kullanılmasının hukuki sonuçları ve hukukun bu dönüşümden nasıl etkileneceği üzerinde durulmaktadır. Son bölümde ise yönetimin geleceği üzerine düşüncelerin yer altığı bir karar ağacı tasarımı içeren interaktif bir bölüme yer verilmektedir. Artificial intelligence technologies are preparing to influence many human-dominated and human-related fields. These fields include medicine, law, education, engineering as well as commerce. Artificial intelligence technologies are on the way to create a new commercial order and understanding that will shake up the traditional structure of corporate law. In particular, the efficiency and speed of artificial intelligence technologies that automate decision-making processes have led companies to tend to use these systems both by developing and marketing them and by incorporating them. In this way, this self-sustaining cycle has led companies with strong capital structures to move towards the field of artificial intelligence, and the scope of research has been gradually expanded. This orientation in companies and the high potential of rapidly developing artificial intelligence technologies to affect traditional company structures have revealed the necessity of conducting an examination on the future of company law. Our study focuses on the use of artificial intelligence technologies in company management and its legal consequences, and the subject is examined under four main sections. In the introduction, the subject, importance, purpose, scope and systematics of the study are briefly explained, and the conceptual framework of artificial intelligence and company management is given. In the first part, the interaction of corporate law and artificial intelligence technologies is examined. In this section, the interaction of artificial intelligence technologies with commercial law and company law is examined, the effects of digitalization on corporate law are discussed, especially within the framework of the transformation in company structures and conflicts of interest. In the second part, the use of artificial intelligence technologies in company management is examined as a process. In this section, where the acquisition of artificial intelligence technologies suitable for the company and the methods of using these technologies in company management are investigated, starting from the decision to use, all technical, legal and commercial expectations and uncertainties are investigated. The third chapter focuses on the legal consequences of the use of artificial intelligence technologies in company management and how the law will be affected by this transformation. In the last part, there is an interactive section that includes a decision tree design with thoughts on the future of management.
Keywords: AI; Anonim şirketler; Artificial Intelligence; Bilgi ve belge yönetimi; Bilgi yönetim sistemi; Bilgi yönetimi; Capital companies; Commercial companies; Financial data management system; Finansal veri yönetim sistemi; Hukuki sorumluluk; Information and records management; Information management; Information management system; Institutional responsibility; Inteligência artificial; Intelligence Artificielle; Joint stock company; Kurumsal sorumluluk; Legal responsibility; Sermaye şirketleri; Ticari şirketler; Yapay zeka

Yönetim kurulu üyelerinin şahsî sorumluluğuna ilişkin davalarda maddî hukukun usûl hukukuyla etkileşimi - Eski̇ocak, Ali (Galatasaray Üniversitesi, 2022)
Les membres du conseil d'administration, qui sont l'organe représentatif et exécutif de la société anonyme, sont investis de pouvoirs et d'attributions étendus à tous les stades de leur activité (Code de Commerce turc art. 365, art. 374). En cas de perte résultant de la violation de ces obligations, il est inévitable que la responsabilité soit mise en avant. Ceci est principalement une conséquence naturelle de la règle générale de "l'équilibre autorité-responsabilité". Dans ce contexte, l'existence et l'effectivité des actions en responsabilité ont un rôle dissuasif pour que les administrateurs ne manquent pas à leurs obligations. D'autre part, en raison du principe de la responsabilité limitée avec les actifs contre les créanciers de la société anonyme (Code de Commerce turc art. 329/1), la protection des actifs est importante pour empêcher les créanciers de subir des pertes. De plus, la question de la responsabilité revêt une importance particulière au regard des principes de gouvernance d'entreprise. Parce que la comptabilité et la responsabilité sont les éléments clés du principe de gouvernance d'entreprise dans les sociétés anonymes qui sont les acteurs les plus importants de la vie économique d'aujourd'hui. Par conséquent, des réglementations détaillées prises en vertu du Code de Commerce turc concernant les obligations et les responsabilités des membres du conseil d'administration; en outre, les dispositions relatives aux poursuites en responsabilité ont été réglementées de manière plus détaillée et systématique et des changements importants ont également été introduits à cet égard. Dans ce cadre, un régime de responsabilité spéciale a été institué pour les administrateurs en dehors des dispositions de responsabilité générale, tandis que les articles 549 à 552 du Code de Commerce turc réglementent la responsabilité spéciale, l'article 553 et les articles suivants du Code de Commerce turc réglementent les dispositions relatives à la responsabilité générale. Ces articles sont relativement larges et complets par rapport à l'ancien code. Diverses études monographiques ont été réalisées en matière de responsabilité juridique des membres du conseil d'administration et ce sujet a été largement examiné dans les travaux sur le droit des sociétés anonymes. Cependant, l'aspect droit matériel de la responsabilité juridique a été principalement examiné dans la doctrine mais les questions liées aux actions en responsabilité et l'aspect procédurale de l'action ont trouvé une place limitée dans la doctrine. Les expressions similaires sont souvent utilisées concernant la nature du droit d'action des actionnaires et créanciers, mais l'aspect procédurale n'est généralement pas examiné avec une explication détaillée, des analyses et une caractérisation. Cependant, cette question est étroitement liée à des questions importantes telles que la relation entre les demandeurs, la litispendance, le jugement définitif, l'exécution du jugement et les caractéristiques des défenses. Dans notre étude, en raison de l'importance des actions en responsabilité et de l'augmentation du nombre des actions en pratique, nous essayons d'expliquer les caractéristiques de l'action en responsabilité (l'aspect procédural) ainsi que l'aspect du droit matériel. Cependant, notre étude n'est pas une thèse de procédure civile, c'est une thèse de droit matériel et il vise à examiner les questions liées au droit procédural en commençant par la nature de la responsabilité, l'engagement de l'action jusqu'à l'exécution du jugement définitif rendu. En conséquence, le sujet de notre étude est de décrire l'aspect de droit substantiel de l'action en responsabilité et d'examiner les domaines où la responsabilité des membres du conseil d'administration intersecter avec le droit procédural. Donc l'objectif de cette étude est l'aspect de droit substantiel de la responsabilité. Les problèmes procéduraux sont examinés dans cette perspective. La responsabilité civile des membres du conseil d'administration a été examiné conformément à l'article 553 et les dispositions suivantes. L'analyse a été faite pour les personnes qui ont le droit d'action avant la déclaration de faillite, mais pas pour les autres qui ont le droit d'action après la déclaration de faillite (administration de la faillite, créanciers). La responsabilité des membres du conseil d'administration et des dirigeants a été prise en considération. Par ailleurs, la responsabilité résultant de la fondation, les cas particuliers de responsabilité régis par l'article 549 et suivants du Code de Commerce turc, la responsabilité de contrôleur qui est régie par l'article 554 du Code de Commerce turc, l'action particulière en responsabilité régie par l'article 193 du Code de Commerce turc, l'action en responsabilité à l'égard d'un groupe de sociétés régi par l'article 202 et les dispositions suivantes du Code de Commerce turc et la révocation des personnes responsables entre elles selon leurs relations internes (action en révocation) sont exclues du champ de cette étude. Notre étude, préparée dans ce contexte, se compose de cinq grandes parties, dans la première partie, les principes de l'aspect droit matériel de l'action en responsabilité ont été examinés. Dans ce cadre, les réglementations légales antérieures et nouvelles en matière de responsabilité, les innovations apportées par la Code de Commerce turc, la base juridique (la source), le but, l'objet, l'intérêt qu'elle protège, ses éléments, sa relation avec divers actions et institutions et ses caractéristiques sont important. La source de responsabilité est basée sur la relation contractuelle entre les membres du conseil d'administration et la société, et les éléments de responsabilité sont l'illégalité, le dommage, le lien de causalité et la faute. La responsabilité des membres du conseil d'administration appartient à l'organe de gestion, est personnelle et fondée sur la faute. Sur cette note, la présomption de responsabilité a été révoquée et le fardeau de la preuve repose sur le demandeur. Alors que le principe de solidarité différenciée a été inclus dans l'article 557 du Code de Commerce turc, il a été mis l'accent sur l'application des dispositions de relation de causalité ainsi que les articles 51-52 du Code des Obligations turc. En ce qui concerne le devoir de diligence, la méthode de référence indirecte au devoir de diligence de l'employé qui était régie par l'article 320 du précédent Code de Commerce a été abandonnée par l'article 369 du Code de Commerce turc, et le devoir de diligence a acquis l'objectivité par l'adoption de « business judgement rule (agir avec diligence, bonne foi et loyauté en decision de gestion)». En outre, dans l'exposé des motifs de l'article, il a été clairement indiqué que le critère de prudence sont pertinents avec la « business judgement rule» Le devoir de diligence est lié à des éléments d'« illégalité » et de « faute ». Par conséquent, cet article signifie l'objectivation de la faute. De ce fait, la frontière entre les éléments d'illégalité et de faute est devenue encore plus incertaine. La délégation de gestion (art.367 du Code de Commerce turc) est une situation qui a un impact sur la responsabilité, avec une délégation valable il y aurait partage responsabilité primaire - responsabilité de surveillance (art. 553/2 du Code de Commerce turc). La nouvelle règle, régie par l'article 557/2 du Code de Commerce turc qui prévoit qu'une action en justice peut être intentée pour l'ensemble du dommage et qu'il peut être demandé au juge de déterminer l'indemnisation de chaque défendeur dans une même action en justice, est importante pour fixer qu'il n'est pas nécessaire que le demandeur tienne compte du principe de solidarité différenciée, et que ce principe est une règle qui ne s'adresse qu'au juge et à la décision qu'il établira. Dans la deuxième partie, les caractéristiques du droit d'intenter une action en responsabilité, les parties de l'action et les modalités d'exercice du droit d'action sont discutées. La caractéristique du droit d'action qui pourrait être exercé par d'autres personnes que la société est importante. Le résultat est étroitement liée aux questions critiques telles que les défenses qui pourraient être invoquées par les défendeurs, et avec quelles défenses pourraient être invoquées contre quel demandeur, la relation entre les demandeurs, la litispendance, le jugement définitif, l'exécution du jugement. Après une évaluation détaillée, notre opinion est que les actionnaires et les créanciers ont chacun individuellement un droit substantiel d'engager une action en responsabilité. En outre, la manière d'exercer le droit de la demande réglementé par la loi est également importante. Étant donné qu'il n'y a pas de disposition ou de déclaration restrictive dans la loi concernant la manière de demande du dommage de l'entreprise, il est également possible d'appliquer tous les recours disponibles en vertu du droit de la procédure civile, de l'exécution et de la faillite. Il est possible de demander des mesures provisoires. Bien qu'il existe une réglementation générale quant aux parties à l'action en responsabilité dans la loi, il est important d'examiner ce sujet. A cet égard, l'action intentée par l'actionnaire avant la faillite n'est soumise à aucune condition. Le montant (ratio) de l'action (la part) n'est pas important. En ce qui concerne le défendeur, les défendeurs sont comptés dans la loi. A ce propos, il est important de déterminer qui entrera dans le champ d'application du concept de « dirigeants», qui est réglementé pour être responsable aux côtés des membres du conseil d'administration. La position des personnes qui ont le droit d'action peut varier selon les avis sur la caractéristique du droit d'action. A notre avis, il n'y a pas d'obstacle légal au dépôt d'actions en responsabilité distinctes par des personnes ayant droit d'action, et cette situation ne constitue pas une litispendance. Dans la troisième partie de notre étude, les instruments de défense relatifs aux actions en responsabilité et à la question de la preuve sont abordés. Les moyens de défense sont importants en ce qui concerne l'instance pendante, la détermination de l'existence des éléments de responsabilité et le calcul du montant de l'indemnité. Parmi les conditions d'action, en tant que moyens de défense en matière de droit procédural, la décision de l'assemblée générale et l'intérêt à agir revêtent une importance particulière. À notre avis la décision de l'assemblée générale devait être recherchée comme condition d'action. En outre, bien que l'intérêt à agir soit une condition générale d'action, il prend plus d'importance pour le cette étude, car dans les actions en responsabilité l'événement qui constitue une violation de l'interdiction de l'abus de droit (art. 2 Code Civil turc). En outre, l'adoption du principe de solidarité différenciée a accru l'importance des motifs de défense individuels. Les motifs matériels de la défense peuvent être très divers, tels que le fait de ne pas être investi d'un organe de gestion, la libération, la prescription, la forclusion, l'exécution du devoir de diligence et la délégation de pouvoir. De plus, comme dans tous les procès, la question de la preuve est également très importante dans les actions en responsabilité. Cependant, un système de preuve spécial et une méthode de preuve n'ont pas été prévus en termes des actions en responsabilité. Par conséquent, des questions telles que la charge de la preuve, l'objet de la preuve, l'échelle de la preuve et les preuves propres doivent être déterminées en tenant compte des caractéristiques spécifiques de l'action en responsabilité, et cela a été examiné dans ce cadre dans notre étude. Dans le quatrième chapitre, le déroulement du procès, le jugement et l'exécution du jugement sont expliqués. En particulier, l'accent mis sur le lien de causalité et l'acceptation du principe de solidarité différenciée avec de nouvelles dispositions obligent le juge à procéder à un examen précis. Dans ce contexte, des questions telles que l'impossibilité du contrôle d'opportunité, la mise en œuvre du principe de solidarité différenciée et la prise en compte de la situation des responsables, qui ne sont pas parties au procès, sont les aspects originaux de la procédure. L'effet du jugement à la fin de l'action est également un sujet discuté dans la doctrine. À notre avis, le jugement ne constituera pas res iudicata (l'autorité de la chose jugée) pour les autres actions en responsabilité et les actions en révocation. Cependant, il convient de noter que l'effet de l'intervention en cas de dénonciation d'instance et d'intervention accessoire, pourrait être important en termes d'action en révocation, et de fait, il peut avoir un effet plus important que res iudicata. Une autre question importante est celle de savoir qui a le pouvoir d'exécuter le jugement et les possibilités dans cette question. Le point le plus prénant ici est que le droit de réclamation de l'actionnaire (le demandeur) comprend le pouvoir d'exécuter le jugement, mais le paiement perçu au stade de l'exécution doit être versée à la société. Dans le cinquième chapitre, quelques situations particulières liées aux actions en responsabilité sont examinées. Dans ce contexte, il a été analysé que l'effet du recouvrement partiel ou total du dommage sur les autres parties responsables dans le cadre de diverses possibilités, la transaction et le désistement d'action (la validité et caractère obligatoire), l'examen de la libération d'une ou plusieurs des personnes responsables au sens de l'article 166/3 du Code des obligations turc, la pertinence de la révocation dans le cadre de l'action en responsabilité et les opérations collusoires de l'entreprise dans le cadre de l'action en responsabilité. Notre avis a été indiqué en conjonction avec l'analyse des arguments de la doctrine et de la pratique sur ces questions.
Keywords: Borçlar hukuku; Cases; Davalar; Faulty liability; Hukuki sorumluluk; Kusurlu sorumluluk; Law of obligations; Legal responsibility; Maddi hukuk; Members of the board directors; Procedural law; Responsibility; Sorumluluk; Substantive law; Turkish Commercial Code; Türk Ticaret Kanunu; Usul hukuku; Yönetim kurulu üyeleri

Anonim ortaklıkta yönetim kurulu üyesinin rekabet yasağı - Günaydin Gülteki̇n, Burcu (Galatasaray Üniversitesi, 2022)
This subject matter of this work is the prohibition of competition with the company of members of board of directors in joint stock companies under art. 396 of the Turkish Commercial Code. The prohibition of competition is a limitation on the commercial activities and the freedom of competition of a restricted party who has access to information, means or resources due to the legal relationship between parties which grant the restricted party a leverage in competition with the other. The core idea underlying the prohibition of competition is the necessity to protect the party benefiting from this prohibition against competitive activities of the restricted party. The prohibition of competition bans the restricted party from establishing competition with the party benefiting from the prohibition through competitive actions, ultimately from becoming the competitor of the beneficiary. The said competition relationship will occur in the event the services or products serving the same or similar needs are provided to the entirety or part of the same customers or customer group. Board members in joint stock company, having the prevailing right of access to all information and resources of the company leads to the risk that it may use this power for its own or other parties' benefit instead of that of the company. Hence, the prohibition of competition on board members regulated under article 396 of the Turkish Commercial Code is one of the concrete examples of the duty of loyalty of a board member towards the company aiming to prevent such usages prioritizing the benefit of the member or of a third person over that of the company. The focal point of this work is the determination of the scope of application and conditions of this prohibition as a whole. The first chapter of this thesis aims to convey the conceptual basis of the prohibition of competition. In this scope, we first assessed the economic and legal basis of competition. Economic competition is the race/competition of two or more market actors in a specific market in order to engage in a transaction with its counterparty in the market through offering better prices, conditions, goods or services in order to be superior from its competitors. However, the intention to supersede its competitors and the efforts for this purpose may result in the misuse of the right to compete or in an act limiting or eliminating the competitive environment. The Republic of Turkey provides for a constitutional protection over a person's right to engage in commercial activities and, although not expressly regulated, right to compete. However, as is the case for all rights and liberties, the right and liberty to compete cannot be exercised without any limitation. Second, the scope of the prohibition of competition is assessed. In this regard, we tried to determine the elements of the prohibition of competition, its definition, and its legal categorization. Moreover, a comparison of the prohibition of competition with the provisions governing unjust competition aiming to establish honest and undisrupted competition as well as with the rules of Competition Law aiming to prevent disruption of competition through restrictive actions is provided in order to specify the prominent characteristics of the prohibition of competition. Third, the attributes of the provisions governing the prohibition of competition are assessed. Provisions governing prohibition of competition which do not relate to the public order but to the internal relations of parties, and which serve the personal benefit of the beneficiary, are not of a peremptory nature. The prohibition of competition, which materially limits the liberty of engaging in commercial activities protected under the constitutional law, is of an exceptional nature and hence the provisions governing the prohibition of competition need to be construed in a limited manner. Fourth, the prohibition of competition can be regulated in the letter of a contract through mutual agreement thereon by its parties, or the legislator occasionally provides for a legal provision governing the prohibition of competition by attributing a special importance to this prohibition with respect to a specific relationship between the parties. Last, in this first chapter, we identify the reflections of this prohibition of competition within the scope of the Law of Obligations, and the Law of Corporations. The second chapter of this work takes into consideration the reasons of regulating a prohibition of competition on board members, and its scope of application regarding the persons concerned. In this context we first broadly assessed the position of the board of directors, board members and affiliated commercial auxiliaries in a company. Then, the legislative provisions respectively of German Law, Swiss Law and Turkish Law governing the board members' prohibition of competition are specified. While in German Law, just as is the case in Turkish law, the prohibition of competition of board members is stipulated in § 88 of the German Stock Corporation Act, the Swiss Law does not regulate this prohibition of competition of board members with a statutory provision, nonetheless, this prohibition is accepted by the scholars. Thereafter, the reason for regulating the prohibition of competition of board members is assessed. In this scope, the duty of loyalty of a board member arises from the legal relationship between the member and the corporation being based on the principle of trust. The member must refrain from conflicting its interests with the interests of the corporation, in other words, from conflict of interests, due to its duty of loyalty. When the member engages in competition with the company, the interests of the company and the board member conflict with each other. The member is in a considerably advantageous position in this conflict compared to the company, due to the information and resources to which it has access thanks to its position within the company. For this reason, the duty of loyalty aiming to prevent the conflict of interest between the company and the member lies at the basis of the board member's prohibition of competition. Lastly, in this chapter, the persons subject to the prohibition of competition pursuant to article 396 of the Turkish Commercial Code are identified. In this respect, the members of the board of directors as well as persons to whom management authorities are delegated fall within the scope of the ratione personae of article 396 of the Turkish Commercial Code. The commercial representatives and commercial proxies of a company are prohibited from competition pursuant to the prohibition of competition regarding commercial auxiliaries pursuant to article 553 of the Turkish Code of Obligations. Whereas a shareholder is not subject to the prohibition of competition with the company; this prohibition may only be regulated by a contract subject to the Law of Obligations. Furthermore, when evaluating the prohibition of competition of shareholders, whether the shareholder has a duty of loyalty to the company has been assessed under German Law, Swiss Law and Turkish Law. The third chapter of this work sets forth the scope of application of the prohibition of competition of board members with respect to its subject matter, place, and time. In order for a board member to violate the prohibition of competition with the company, the member must engage in an activity competing with the company. Pursuant to the first paragraph of article 396 of the Turkish Commercial Code, two types of competitive actions of board members are banned. The first type is the member engaging in an action which is a commercial transaction that falls within the scope of the field of activity of the company, on behalf of itself or a third party. Accordingly, all kinds of acts and actions of the member realized on behalf of itself or third parties which fall within the scope of activity of the corporation would constitute the breach of the prohibition. The scope of this prohibition also encompasses joining the managing body of another corporation. Furthermore, depending on the specifics of a concrete case, the same member being an employee of a competitor corporation under a service contract, or providing consultancy services or extending facilities to a competitor, or benefiting from a job opportunity which belonged to the company may also be construed to be within the scope of the prohibition of competition. The second type is the member being engaged as a partner with unlimited liability in a corporation engaging in the same types of commercial activities. In this regard, if a member becomes a partner of an ordinary partnership or a collective corporation, or a partner with unlimited liability of a commandite corporation, which engages in activities that fall within the scope of activities of the joint stock company, the prohibition will be breached. The prohibition of competition of the board member with the company may be lifted by an authorization granted by the general assembly pursuant to article 396 of the Turkish Commercial Code. This permission to compete to be granted to a board member may be in the form of a prior approval or a later acknowledgement (ratification), in an expressed or implied manner. As a result of the member being permitted to compete, article 396 of the Turkish Commercial Code will no longer apply even if the member engages in activities in competition with the company. The prohibition to compete of the board member lasts for the duration of the board membership. Once the membership ends, the parties must conclude an agreement in order to continue the prohibition of competition. The said agreement regarding the prohibition of competition will be subject to form requirements to be valid. Pursuant to the liberty of contract inherent in the Law of Obligations, the parties may freely execute an agreement regarding the prohibition of competition, provided they comply with the provisions in paragraph 2 of article 23 of the Civil Code or article 26 and first paragraph of article 27 of the Turkish Commercial Code. The prohibition to compete of board members is valid as long as they execute the activities of the company, and within the geography where the clientele of the corporation is located. The fourth and last chapter of this work is devoted to the consequences of breach of the prohibition to compete by a board member. If a member of the board of directors violates this prohibition, the consequence of this breach is regulated in the first paragraph of art. 396 of the Turkish Commercial Code. Accordingly, the joint stock company is granted with certain elective rights. Such that, primarily the company may request compensation from the member in breach of the prohibition of competition. Second, it may be requested that the transaction is deemed concluded on behalf of the joint stock company, third, that the benefits arising from the agreement the member concludes on behalf of third parties belong to the joint stock company. In its request for compensation, the joint stock company must prove the action of the board member violating the prohibition of competition, that the corporation suffered losses from this activity, and the causal link between this activity and the loss of the company. In its request for the transaction to be deemed concluded on its behalf, the company requests for the economic consequences of the transactions the member concluded in violation of the prohibition of competition on its behalf. In its request for the benefits arising from the agreement, the company requests that benefits arising from the agreement the member concluded on behalf of third parties are left to itself. At this point, we materially benefited from the German doctrine and jurisprudence in explaining the claims requesting that a transaction is deemed concluded on behalf of the company and that the benefits from the transactions are left to the company. These rights granted in the first paragraph of article 396 of the Turkish Commercial Code are not cumulative but elective. Pursuant to the second paragraph of article 396 of the Turkish Commercial Code, the authority to chose one of the elective rights granted to the company belongs to the members of the board of directors, excluding the member having violated the prohibition of competition. The third paragraph of article 396 of the Turkish Commercial Code regulates a dual prescription period of three months and one year. These periods are with respect to the exercise by the company of its elective right to make a claim. The first is the period of three months whose commencement will be determined based on the knowledge by other members that an action subject to the prohibition of competition is realized or that a board member joined another corporation. The second period is the period of one year commencing from the realization of the action violating the prohibition to compete. This one-year period is independent from other members' knowledge that the prohibition to compete has been breached. The corporation may raise other claims against the member violating the prohibition of competition which are not stipulated under article 396 of the Turkish Commercial Code. Accordingly, the corporation may request that the member violating the prohibition of competition through joining a competing corporation as a partner with unlimited liability or joining the managing body of a competitive corporation resigns from this corporation or managing body. Further, the company may dismiss the member violating the prohibition of competition from board membership. Again, the company may initiate a lawsuit to cease the ongoing violation of the prohibition of competition by a board member, or a lawsuit of preclusion prior to probable breaches which have not yet occurred. In this chapter, lastly, the fourth paragraph of article 396 of the Turkish Commercial Code is assessed. This paragraph regulates that provisions governing liability of the members of the board of directors are reserved. This is a new provision which was not present in the abrogated Turkish Commercial Code no. 6762, newly introduced under the Turkish Commercial Code. In this context, we tried to determine the purpose and characteristics of this provision and concluded this work.
Keywords: Administrateurs; Anonim şirketler; Board of directors; Competition prohibition; Concurrence (interdiction); Joint stock company; Members of the board directors; Rekabet yasağı; Société par actions; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yönetim kurulu; Yönetim kurulu üyeleri

Hâkim pay sahibinin azınlığı şirketten çıkarma hakkı (Squeeze-out) - Keski̇n, Harun (Ankara Üniversitesi, 2022)
Klasik anlamdaki şirketten çıkarma düzenlemeleri, "haklı sebep" temeline dayanmaktadır. Bu düzenlemelerin en tipik özelliği, düzenlemiş oldukları çıkarma hakkı ile şirketin feshi kurumu arasında bir bağlantıya yer vermiş olmalarıdır. Bu bağlantı, haklı sebebe dayalı çıkarma düzenlemelerinin hizmet ettiği birincil amacı da ortaya koymaktadır: Şirketin devamlılığını sağlamak suretiyle ortaklar arasındaki menfaatler dengesi korumak. Türk hukukuna 6102 sayılı Türk Ticaret Kanunu ve 6362 sayılı Sermaye Piyasası Kanunu ile kazandırılan "squeeze-out" müessesesi ise daha farklı bir kuramsal temele dayanmaktadır. Bu müessese ile, şirkette genellikle %90-95 arasında nitelikli bir pay ve/veya oy oranına ulaşmış olan hâkim pay sahibine, azınlığın paylarını herhangi bir sebep göstermeden iktisap edip, onu şirketten çıkarma hakkı tanınmıştır. Böylece çıkarmanın ekseni, "haklı sebep" olgusundan "hâkimiyet" olgusuna kaymıştır. Kanun koyucuların bu şekilde bir çıkarma hakkını öngörmelerindeki temel sebep ise kurumsal nitelikte bazı amaçları gerçekleştirmek isteyen hâkim konumdaki pay sahiplerine bir imkân sunmaktır. Tezimizde, klasik anlamdaki çıkarma müesseselerinin dayanmış olduğu kuramsal temelden ayrılan "squeeze-out" kurumunun kuramsal temeli, düzenlemenin hangi amaçlarla öngörüldüğü meseleleri ele alınmakta; bu bağlamda, kurumun karşılaştırmalı hukuktaki ne şekilde düzenlendiği, kurumun ortaya çıkardığı sorunlar ve bu sorunların çözümüne yönelik önerilere yer verilmektedir. The classic rules designed for exclusion of a partner has a simple theoretical basis: A/an justified/objective reason (or in other words "good cause"). The most typical feature of these rules is they build a bridge between the exclusion right and the dissolution of the company. This bridge also shows the the primary purpose served by these rules which is to maintain the balance of interests among the partners by ensuring the continuity of the company. In comparison with the classical rules, the "squeeze-out" rules which have been introduced into Turkish law with the Turkish Commercial Code No. 6102 and the Capital Markets Law No. 6362, have a different theoretical basis. The controlling shareholder who has reached a qualified percentage of capital and/or voting rights (usually %90-95), has been granted the right to acquire the minority's shares without asserting any justified reason and exclude him from the company. Thus the idea behind the exclusion has been changed from "good cause" to the "dominance/control". The main reason for designing such an exclusion right is to provide an opportunity to the controlling shareholders trying to achieve institutional objectives in the company. In our thesis, the theoretical basis of the "squeeze-out" rules and the reasons for designing such a new exclusion right will be examined within the framework of other squeeze-out rules in comparative law. Within this context, the most common problems in squeeze-outs and suggestions for solving these problems are analyzed.
Keywords: Actionnaire majoritaire; Actionnaire minoritaire; Anonim şirketler; Azınlık hakları; Capital companies; Dismissal from the partnership; Dominant position; Exclusion; Hakim durum; Joint stock company; Kanunlar 6362 sayılı; Laws 6362 numbered; Limited company; Limited şirketler; Minority rights; Ortaklıktan çıkarılma; Satın alma hakkı; Sermaye şirketleri; Société commerciale; Squeeze-out right; Turkish commercial law; Türk ticaret hukuku

Anonim şirketlerde ilişkili taraf işlemleri - Şi̇mşek, Bahar (İstanbul Üniversitesi, 2022)
İlişkili taraf işlemlerine ilişkin özel düzenlemelerle şirketin varlıklarının ilişkili taraflara aktarılması ve şirketin ve şirketin bütün menfaat sahiplerinin hâkim pay sahipleri ve yöneticiler tarafından sömürülmesinin engellenmesi amaçlanır. Bu amaçla ilişkili taraf işlemleriyle ilgili Sermaye Piyasası Kanunu'nda etraflıca bir düzenleme getirilmiş ve önemli bazı işlemler için prosedür öngörülmüştür. Çalışmamız, esaslı düzenleme Sermaye Piyasası Kanunu'nda yer aldığı için bu düzenleme temel alınarak şekillendirilmiştir. Ancak sadece halka açık şirket değil; halka kapalı şirketler yönünden de konu incelenmiş, ilişkili taraf işlemi sayılabilecek Türk Ticaret Kanunu'nda ve diğer kanunlarda yer alan diğer düzenlemelere de yer verilmiştir. Tez dört bölümden oluşmaktadır. İlk bölümde ilişkili taraf işlemi kavramı genel olarak açıklanmış, ilişkili taraf işlemleriyle ilgili düzenlemelere neden ihtiyaç olduğu hususu ortaya koyulmaya çalışılmıştır. Bu kapsamda benzer kavramlarla karşılaştırılmış ve Avrupa Birliği ve çeşitli ülkelerde düzenlemeler incelenmiştir. Nihai olarak Türk hukukunda ilişkili taraf işlemlerinin tarihsel sürecine yer verilmiştir. İkinci bölümde yasal düzenlemelerdeki ilişkili taraf ve ilişkili taraf işlemi kavramı ele alınmıştır. Üçüncü bölümde ise ilişkili taraf işlemleriyle ilgili Sermaye Piyasası Kanunu, Türk Ticaret Kanunu ve bazı özel kanunlarda yer alan düzenlemeler incelenmiş, ilişkili taraf işlemleri için öngörülen prosedürel korumalar açıklanmıştır. Dördüncü bölümde ise hukuka aykırı ilişkili taraf işlemlerinin sonuçları incelenmiş ve ilgililerin sorumluluğuna yer verilmeye çalışılmıştır. Special regulations regarding related party transactions aim to prevent the transfer of the assets of the joint stock company to the related parties and thus prevent the exploitation of all the stakeholders of the company by the controlling shareholders and managers. For this purpose, a comprehensive regulation has been introduced in the Capital Markets Law regarding related party transactions and a procedure has been envisaged for some significant transactions. Since the main regulation is contained in the Capital Markets Law, our thesis has been shaped based on this regulation. However, this thesis has not examined the subject only for public companies; it has also examined it in terms of non-public companies, and other regulations in the Turkish Commercial Code and other laws, which can be considered as related party transactions. The thesis consists of four parts. In the first part, the concept of related party transactions is explained in general and the reason for the need for regulations regarding related party transactions is tried to be revealed. In this context, related party transactions have been compared with similar concepts and the regulations in the European Union and various countries have been examined. Finally, the historical process of related party transactions in Turkish law is examined. In the second chapter, the concept of related party and related party transactions as defined in legal regulations is discussed. In the third section, the regulations contained in the Capital Markets Law, the Turkish Commercial Code and some special laws related to related party transactions are examined and the procedural protections provided for related party transactions are explained. In the fourth chapter, the results of unlawful related party transactions are examined and the liability of the related parties is tried to be included.
Keywords: Anonim şirketler; Camouflage of earning distribution; Joint stock company; Société par actions; Turkish capital market; Turkish commercial law; Türk sermaye piyasası; Türk ticaret hukuku; Örtülü kazanç dağıtımı

Anonim ortaklıkta pay sahibinin bilgi alma ve inceleme hakkı - Sümer, Burak (Hacettepe Üniversitesi, 2022)
Anonim ortaklıkta her pay sahibi genel kurulda, yönetim kurulundan şirketin işleri; denetçilerden ise denetimin yapılma şekli ve sonuçları hakkında bilgi alma talebinde bulunma hakkına sahiptir. Ayrıca her pay sahibinin şirketin ticari defterlerini ve yazışmalarını, sorusunu ilgilendiren kısımları ile sınırlı olarak inceleyebilme hakkı bulunmakla birlikte, bunun için genel kurulun açık izni veya yönetim kurulunun bu hususta kararı gereklidir. Pay sahibinin bilgi alma ve inceleme hakkının reddi, talep edilen bilginin şirket sırlarının açıklanmasına veya korunması gereken diğer şirket menfaatlerinin tehlikeye girmesine neden olabilecek ise söz konusu olabilir. Bilgi alma ve inceleme talebinin cevapsız bırakılması, haksız olarak reddedilmesi, ertelenmesi veya pay sahibinin kanunda düzenlendiği şekilde bilgi alamaması halinde, hakkın açılacak bir dava ile mahkeme aracılığıyla kullanılması da mümkündür. Çalışmamız dört bölümden oluşmaktadır. İlk bölümde bilgi alma ve inceleme hakkının genel nitelikleri ile karşılaştırmalı hukuktaki düzenlenme şekli; ikinci bölümde hakkı etkileyen ilkeler ve hakkın düzenlenme amacı; üçüncü bölümde bilgi alma ve inceleme hakkının kullanılması ve hakkın sınırları; dördüncü ve son bölümde ise hakkın ihlalinin hukuki sonuçları ele alınmıştır. At the general meeting, any shareholder of a joint stock company is entitled to information from the board of directors on the affairs of the company and from the external auditors on the methods and results of their audit. Also the company ledgers and business correspondence, limited to the parts about the question may be inspected only with the express authorisation of the general meeting or by resolution of the board of directors. It may be refused where providing it would jeopardise the company's trade secrets or other interests warranting protection. If the request for information and examination is left unanswered, unfairly rejected, postponed or if the shareholder is unable to obtain information as regulated in the law, it is also possible to exercise the right through a lawsuit to be filed. Our study consists of four parts. In the first part, the general characteristics of the right to information and examination and the way it is regulated in comparative law; in the second part, the principles affecting the right and the purpose of regulation of the right; the exercise of the right to receive and review information and the limits of the right in the third part; In the fourth and last chapter, the legal consequences of the violation of the right are discussed.
Keywords: Anonim ortaklıklar; Bilgi alma ve inceleme hakkı; Company law; Incorporated companies; Pay sahipleri; Right to information and examination; Shareholders; Turkish commercial law; Türk ticaret hukuku; Şirketler hukuku

Halka açık anonim şirketler bakımından şirketler topluluğunda ortak nakit ve hizmet kullanımının hukuki sonuçları - Üzeler Demi̇rağ, Rabia Sanem (İhsan Doğramacı Bilkent Üniversitesi, 2022)
Bu çalışmanın temel amacı şirketler topluluğunda yer alan halka açık şirketlerin topluluk şirketleri ile ortak nakit ve hizmet kullanımına yönelik işlemlerinin sermaye piyasası mevzuatı açısından sınırlarının ve hukuki sonuçlarının tespit edilmesidir. Bu doğrultuda sermayenin oluşturulması ve malvarlığının korunması kuralları kapsamında ortak nakit kullanımı uygulamalarının sınırları, ilişkili taraf işlemlerine ilişkin düzenlemeler ve örtülü kazanç aktarımı yasağı çerçevesinde değerlendirilmiştir. İlaveten, şirketler topluluğunda maliyet tasarrufu sağlayan ve topluluğun ortak stratejiler çerçevesinde yönetilmesi bakımından gerekli olan ortak hizmetler nedeniyle yapılan ödemelerin tutarlarının belirlenmesine ilişkin esaslar örtülü kazanç aktarımı yasağı bağlamında ele alınmıştır. Son olarak, hukuka aykırılığa yol açan ortak nakit ve hizmet kullanımı uygulamalarına yönelik Sermaye Piyasası Kurulu'nun müdahale yetkileri ve şirketler topluluğunda hâkim şirketin bağlı şirketin kaybını denkleştirebilmesi olanağının halka açık şirketlerde uygulama alanı bulmasının hukuken hangi hâllerde gündeme gelebileceği irdelenmiş ve halka açık şirketlerin dâhil oldukları şirketler topluluklarında ortaya çıkan menfaat çatışmalarının dengelenmesine yönelik değerlendirme ve düzenleme önerilerinde bulunulmuştur. The main purpose of this study is to determine the legal limits and consequences of the shared use of cash and services within corporate groups for publicly held companies' in relation to capital markets legislation. In this respect, the legal limits of transactions which enables sharing cash among group companies with respect to rules on formation and protection of capital of publicly held companies is reviewed within the context of related party transactions and cases which may result in disguised profit distribution is evaluated. Additionally, the use of shared services in corporate groups which provides significant savings and is necessary for developing common strategies is examined in order to determine which principles must be adhered to while charging for these services with regard to the ban on disguised profit distribution. Furthermore, Capital Markets Boards' intervention powers regarding the shared use of cash and services which results in violation of the law is evaluated and the parent company's opportunity of balancing the disadvantages of the subsidiary is assessed for publicly held companies. Finally, legislative amendments have been proposed in order to balance the conflicts of interest which arises where a publicly held company is part of a corporate group.
Keywords: Anonim şirketler; Capital Market Board; Capital Market Law; Cash flow; Cash management; Cosourcing; Halka açık ortaklıklar; Joint stock company; Nakit akışı; Nakit yönetimi; Ortak kaynak kullanımı; Public held companies; Sermaye Piyasası Kanunu; Sermaye Piyasası Kurulu; Turkish commercial law; Türk ticaret hukuku